2016
DOI: 10.1155/2016/4867092
|View full text |Cite
|
Sign up to set email alerts
|

Antcin K, a Triterpenoid Compound from Antrodia camphorata, Displays Antidiabetic and Antihyperlipidemic Effects via Glucose Transporter 4 and AMP‐Activated Protein Kinase Phosphorylation in Muscles

Abstract: The purpose of this study was to screen firstly the potential effects of antcin K (AnK), the main constituent of the fruiting body of Antrodia camphorata, in vitro and further evaluate the activities and mechanisms in high-fat-diet- (HFD-) induced mice. Following 8-week HFD-induction, mice were treated with AnK, fenofibrate (Feno), metformin (Metf), or vehicle for 4 weeks afterward. In C2C12 myotube cells, the membrane GLUT4 and phospho-Akt expressions were higher in insulin and AnK-treated groups than in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…Previous research has confirmed the hypolipidemic effect of AC (17,20,31,32), supporting the results of the present study that indicated a decrease in plasma FFA levels. To establish the SIIR animal model, steroids were administered, causing an increase in plasma FFA levels and the development of insulin resistance (11,25).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous research has confirmed the hypolipidemic effect of AC (17,20,31,32), supporting the results of the present study that indicated a decrease in plasma FFA levels. To establish the SIIR animal model, steroids were administered, causing an increase in plasma FFA levels and the development of insulin resistance (11,25).…”
Section: Discussionsupporting
confidence: 92%
“…With respect to signal transduction proteins, AC caused an increase in IRS-1, PI3K and GLUT-4. Previous studies have indicated that AC stimulates AMPK to enhance GLUT-4 translocation and activates the peroxisome proliferator activated receptor α (PPARα) to decrease plasma FFA levels, which may complement the insulin signaling pathway to result in a hypoglycemic effect and improvement in insulin resistance (18,20,32,34). In our previous studies, we also used the SIIR animal model to test the hypoglycemic effect of the Xylaria nigripes (Xn) fungus and the Gardenia jasminoides (GJ) plant (26,35).…”
Section: Discussionmentioning
confidence: 99%
“…The current study showed that diabetic rats had a significant increase in fasting glucose and increase in the insulin level when matched with Con and Nano-PAC5-treated groups and had similarity with previous a report stating that Antcin K (a triterpenoid compound from A. camphorata) reduced the blood glucose and insulin level. 58 In addition, dehydroeburicoic acid 59 and eburicoic acid 24 (triterpenoid compound from A. camphorata) prevented diabetes by the regulation of GLUT4 and AMP-activated protein kinase phosphorylation in STZ-induced diabetic mice.…”
Section: No and Superoxide Productionmentioning
confidence: 99%
“…Due to the abundance of antcin K in wood-cultivated, as well as in dish-cultivated, A. cinnamomea, many bioactivities of antcin K have been found [3][4][5][6][7][8]. In contrast, few studies on antcamphin E and antcamphin F have been reported, due to their rarity.…”
Section: Discussionmentioning
confidence: 99%